Plasma levels of some vitamins and elements in aborted ewes in Elazi? Region - Naziro?lu, Mustafa; Çay, Mehmet; Karataş, Fikret; Çimtay, Ibrahim; Aksakal, Mesut (My University, 1998)
This study, we aimed to examine the levels of vitamin A, E. selenium, zinc, copper, phosphorus, magnesium and total protein in blood of aborted ewes. Aborted and control (non aborted) Akkaraman ewes were used in living different regions of Elazi?. The levels of selenium, zinc, copper, phosphorus, magnesium, total protein, vitamin A and E were measured in plasma samples of aborted and control animals. Present findings showed that concentration of vitamin E, selenium, copper, magnesium (P<0.001) and phosphorus (P<0.05) were-significantly lower in aborted ewes than in control. However, there was no significant differences in zinc, vitamin A and total protein levels showed between two groups. As a results indicated that the levels of vitamin E, selenium, copper, phosphorus and magnesium were significantly lower in aborted ewes than control ewes in Elazig region and the high incidence of ewe abortion is believed to be due to deficiency of vitamin E. selenium, copper, phosphorus and magnesium.
Keywords: Abortion; Ewe; Selenium; Vitamin a; Vitamin e